Assessment of the Use of ©GORA Gestures in Language Communication Therapy of a Child with Impaired Speech Development (A Therapist’s Perspective) - Aleksandra Karwowska; Gabriela Lorens (Konteksty Pedagogiczne, 2020)
The purpose of this article was to evaluate the use of articulatory gestures by specialists in language communication therapy. Impaired speech development significantly impedes the individual’s language communication, leading to developmental deficits in the emotional, cognitive and social spheres. Articulatory gestures are an effective method supporting therapy when working with people with language communication disorders. They help one overcome deficits in the development of motor functions and/or auditory perception, which are the underlying difficulties in mastering the language. Thanks to this, they stimulate the development of the child’s speech and language, building and developing communication and language competencies. The authors of this article verified their observations and thoughts by conducting surveys among speech therapists supporting language communication therapy with articulatory gestures.